The dynamics of inductively accelerated electrons in the U-3M torsatron - Tarasov, M.I.; Tarasov, I.K.; Sitnikov, D.A.; Pashnev, V.K.; Goncharov, I.G.; Listopad, V.M.; Lymar, N.V.; Shtan’, A.F.; Solodovchenko, S.I. (Вопросы атомной науки и техники, 2012)
Additional experimental data for the runaway electrons flow in the Uragan-3M torsatron were obtained. In particular the synchrotron and ultrahigh frequency radiation were measured. Also the flow current dynamics was studied by Rogovski coil and toroidal loop. Finally the experiments with the runaway flow stimulation were carried out.